2020
DOI: 10.1177/1049732320930195
|View full text |Cite
|
Sign up to set email alerts
|

Emerging From the “Ku:” Fluctuating in Adjusting With Breast Cancer—A Post-Traumatic Growth Theory Situated Within Chinese Culture

Abstract: This purpose of the study was to construct a model (theory) to understand Chinese women’s adjustment process in living with breast cancer. A constructivist grounded theory method was adopted in this study. A total of 24 women were recruited through purposive and theoretical sampling. Semi-structured, audio-recorded interviews were undertaken in Chinese and transcribed. Initial coding, focused coding, and theoretical coding approaches were used to identify subcategories and categories, and to construct the emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
0
10
1
Order By: Relevance
“…To help cancer survivors achieve psychological growth, several studies developed effective interventions such as supportive expressive therapy (Ramos et al, 2017), mindfulness‐based stress reduction (Kenne Sarenmalm et al, 2017), and narrative nursing (Shulin et al, 2017) but these interventions require certain application conditions and personnel qualifications. A qualitative study revealed that “emerging from suffering” is the main cognitive and emotional process of post‐traumatic growth for Chinese women with breast cancer and self‐disclosure, a culturally specific feature, contributes to their adjustment (Zhai et al, 2020). Thus, implementing and evaluating a PTG intervention based on Eastern cultural contexts is imperative for Chinese women with breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…To help cancer survivors achieve psychological growth, several studies developed effective interventions such as supportive expressive therapy (Ramos et al, 2017), mindfulness‐based stress reduction (Kenne Sarenmalm et al, 2017), and narrative nursing (Shulin et al, 2017) but these interventions require certain application conditions and personnel qualifications. A qualitative study revealed that “emerging from suffering” is the main cognitive and emotional process of post‐traumatic growth for Chinese women with breast cancer and self‐disclosure, a culturally specific feature, contributes to their adjustment (Zhai et al, 2020). Thus, implementing and evaluating a PTG intervention based on Eastern cultural contexts is imperative for Chinese women with breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…One important point to note is that PTG could differ across cultures (Spencer-Oatey & Kádár, 2016). There is evidence showing that Chinese sociocultural context may influence the appraisal of stressors, coping strategies and processes, and thus PTG (Zhai et al, 2020; Zhang et al, 2020). For example, unfortunate or traumatic events, such as cancers, are perceived as the result of karma in Chinese culture.…”
mentioning
confidence: 99%
“…But that does not deprive you from being what you can do, who you are. It is my meaning for that [70].…”
Section: Want To Spread What I Learnt From My Life If I Can Give Some...mentioning
confidence: 99%
“…I feel that after becoming ill, I cherish what I need to treasure more and spend more time with my families and children [70].…”
Section: Acceptance Of Needing Othersmentioning
confidence: 99%